MR imaging of phenylketonuria. - Shaw, D W; Maravilla, K R; Weinberger, E; Garretson, J; Trahms, C M; Scott, C R (American Journal of Neuroradiology, 1991)
Cranial MR imaging was performed on nine patients (13-27 years old) with classical phenylketonuria in order to define the spectrum of abnormal findings and to determine if these could be related to clinical or biochemical findings. MR abnormalities consistent with demyelination were found in varying degrees in a distribution corresponding to previous histopathologic studies. Specifically, increased signal was seen on T2-weighted sequences, most marked in the periventricular deep cerebral white matter. These changes were more prominent posteriorly, especially about the optic radiations. Comparison with clinical history and MR findings in this small series revealed that patients with adequate dietary control of phenylalanine levels had less severe white matter abnormalities than did patients with poorly controlled phenylalanine intake.